The extracellular matrix as a multitasking player in disease. (11th April 2019) - Theocharis, Achilleas D.; Manou, Dimitra; Karamanos, Nikos K.
Abstract : Extracellular matrices (ECMs) are highly specialized and dynamic three‐dimensional (3D) scaffolds into which cells reside in tissues. ECM is composed of a variety of fibrillar components, such as collagens, fibronectin, and elastin, and non‐fibrillar molecules as proteoglycans, hyaluronan, and glycoproteins including matricellular proteins. These macromolecular components are interconnected forming complex networks that actively communicate with cells through binding to cell surface receptors and/or matrix effectors. ECMs exert diverse roles, either providing tissues with structural integrity and mechanical properties essential for tissue functions or regulating cell phenotype and functions to maintain tissue homeostasis. ECM molecular composition and structure vary among tissues, and is markedly modified during normal tissue repair as well as during the progression of various diseases. Actually, abnormal ECM remodeling occurring in pathologic circumstances drives disease progression by regulating cell–matrix interactions. The importance of matrix molecules to normal tissue functions is also highlighted by mutations in matrix genes that give rise to genetic disorders with diverse clinical phenotypes. In this review, we present critical and emerging issues related to matrix assembly in tissues and the multitasking roles for ECM in diseases such as osteoarthritis, fibrosis, cancer, and genetic diseases. The mechanisms underlying the various matrix‐based diseases are also discussed. Research focused on the highly dynamic 3D ECM networks will help to discover matrix‐related causative abnormalities of diseases as well as novel diagnostic tools and therapeutic targets. Abstract : The extracellular matrix (ECM) is a complex and dynamic scaffold that provides structural support to cells. The ECM is composed of a variety of fibrous proteins and proteoglycans that form a structural scaffold and generate chemical and mechanical signals that are essential to maintain tissue homeostasis. Abnormal remodeling of tissues results in alterations in ECM structure and function, which ultimately promotes the development of common diseases such as fibrosis, osteoarthritis, and cancer.